Visualization & its applications in computer graphics [ - Castleberry, Laverna (New York : Learning Press, 2014)
This book focuses on concepts of visualization & its applications in computer graphics
1. Visualization (computer graphics) -- 2. Volume rendering and visual analytics -- 3. Table (information) and visual communication -- 4. Data flow diagram and data visualization -- 5. Information visualization and interactive visualization -- 6. Information graphics -- Tags cloud -- 8. Visual language -- 9. Visualization software and voxel -- 10. IBM openDX and music visualization
Keywords: Computer graphics